Do not isolate all but the infected, old and the ill - Finsterer, Josef (Jour Med Resh and Health Sci, 2021)
Generally, there are two main strategies to cope with the ongoing SARS-CoV-2 pandemia (mortality 2.14% as per January 22nd (96,2 million infected patients, 2,058.534 deaths worldwide) [1,2]).